The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1158/0008-5472.can-19-0119
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Characterization of SY-1365, a Selective, Covalent Inhibitor of CDK7

Abstract: Recent studies suggest that targeting transcriptional machinery can lead to potent and selective anticancer effects in cancers dependent on high and constant expression of certain transcription factors for growth and survival. Cyclin-dependent kinase 7 (CDK7) is the catalytic subunit of the CDK-activating kinase complex. Its function is required for both cell-cycle regulation and transcriptional control of gene expression. CDK7 has recently emerged as an attractive cancer target because its inhibition leads to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
118
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(128 citation statements)
references
References 42 publications
4
118
0
Order By: Relevance
“…As a whole CDK7 inactivation dismantles two mechanisms needed for medulloblastoma proliferation and survival. These data are particularly relevant given the recent development of clinical grade CDK7 inhibitors (Hu et al, 2019a;Hu et al, 2019b;Patel et al, 2018). CDK7 inhibition with SY-5609 has already entered clinical trials (NCT04247126).…”
Section: Discussionmentioning
confidence: 99%
“…As a whole CDK7 inactivation dismantles two mechanisms needed for medulloblastoma proliferation and survival. These data are particularly relevant given the recent development of clinical grade CDK7 inhibitors (Hu et al, 2019a;Hu et al, 2019b;Patel et al, 2018). CDK7 inhibition with SY-5609 has already entered clinical trials (NCT04247126).…”
Section: Discussionmentioning
confidence: 99%
“…Critically, ovarian cancer oncogene CCNE1 was downregulated -2.0 and -2.2 fold following PAX8 and SOX17 depletion, respectively, consistent with CCNE1 being a target of these MTFs. Rb pathway alterations predict responses of patient derived xenograft models to SY-1365 (Hu et al, 2019), a covalent CDK7 inhibitor currently in clinical trials for advanced breast and ovarian cancer (NCT03134638). While we validated 3 factors in OV, additional MTFs may contribute to the transcriptional circuitry of HGSOC.…”
Section: Discussionmentioning
confidence: 99%
“…There is one CDK-inhibitor (SY-1365) in phase I clinical trial for ovarian and breast cancer (Hu et al, 2019). The inhibition with SY-1365 leads to decreased levels of multiple oncogenic transcription factors and it exhibits the inhibitory effects on multiple cancer cell lines at nanomolar level.…”
Section: Inhibitors Of Transcription Factor Gene Expressionmentioning
confidence: 99%
“…The inhibition with SY-1365 leads to decreased levels of multiple oncogenic transcription factors and it exhibits the inhibitory effects on multiple cancer cell lines at nanomolar level. In addition, mouse xenograft studies showed modest antitumor activity in both AML as well as ovarian cancer, and a synergistic effect with venetoclax (Hu et al, 2019).…”
Section: Inhibitors Of Transcription Factor Gene Expressionmentioning
confidence: 99%